The State of Artificial Intelligence Research in the Context of National Security: Bibliometric Analysis and Research Agenda - Wamba, Samuel Fosso; Bawack, Ransome Epie; Carillo, Kevin Daniel André (Digital Transformation for a Sustainable Society in the 21st Century, 2019)
Artificial intelligence (AI) is a growing research topic in national security due to the growing need for peaceful and inclusive societies, as well as for the maintenance of strong institutions of justice. As e-societies continue to evolve due to the advancements made in information and communication technologies (ICT), AI has proven crucial to guarantee the development of security measures, especially against growing cyberthreats and cyberattacks. This relevance has been translated into an explosive growth of AI applications for the improvement of decision support systems, expert systems, robotics, surveillance, and military operations that aim at ensuring national security. However, there is no bibliometric research on AI in national security, especially one that highlights current debates on the topic. This paper presents an overview of research on AI and national security, with emphasis on the research focus areas and debates central to research on the topic. We analyzed 94 references collected from the Web of Science (WoS) Core Collection and used VOS viewer software to analyze them. Based on these analyses, we identified 7 focus areas and 8 debates on AI in national security. We also identified the state and evolution of research on the topic in terms of main journals, authors, institutions, and countries. Our findings help researchers and practitioners better understand the state of the art of AI research on national security, and guides future research and development projects on the topic.